Self-weighing in weight management interventions: A systematic review of literature. Issue 5 (September 2016) - Shieh, Carol; Knisely, Mitchell R.; Clark, Daniel; Carpenter, Janet S.
Summary: Background: Self-weighing increases a person's self-awareness of current weight and weight patterns. Increased self-weighing frequency can help an individual prevent weight gain. Literature, however, is limited in describing variability in self-weighing strategies and how the variability is associated with weight management outcomes. Aim: This review analyzed self-weighing in weight management interventions and the effects of self-weighing on weight and other outcomes. Methods: Twenty-two articles from PubMed, CINAHL, Medline, PsychInfo, and Academic Search Premier were extracted for review. Results: These 22 articles reported findings from 19 intervention trials, mostly on weight loss or weight gain prevention. The majority of the reviewed articles reported interventions that combined self-weighing with other self-monitoring strategies (64%), adopted daily self-weighing frequency (84%), and implemented interventions up to six months (59%). One-half of the articles mentioned that technology-enhanced or regular weight scales were given to study participants. Of the articles that provided efficacy data, 75% of self-weighing-only interventions and 67% of combined interventions demonstrated improved weight outcomes. No negative psychological effects were found. Conclusions: Self-weighing is likely to improve weight outcomes, particularly when performed daily or weekly, without causing untoward adverse effects. Weight management interventions could consider including this strategy.